Uptake of 18F-FET and 18F-FCH in Human Glioblastoma T98G Cell Line after Irradiation with Photons or Carbon Ions - Pasi, Francesca; Persico, Marco Giovanni; Buroni, Federica Eleonora; Aprile, Carlo; Hodolic, Marina; Corbella, Franco; Nano, Rosanna; Facoetti, Angelica; Lodola, Lorenzo (Contrast Media & Molecular Imaging, 2017)
The differential diagnosis between recurrence of gliomas or brain metastases and this phenomenon is important in order to choose the best therapy and predict the prognosis but is still a big problem for physicians. The new emerging MRI, CT, and PET diagnostic modalities still lack sufficient accuracy. Radiolabeled choline and amino acids have been reported to show great tumor specificity. ​We studied the uptake kinetics of [18F]fluoromethyl-choline (FCH) and O-(2-[18F]fluoroethyl)-L-tyrosine (FET) by the T98G human glioblastoma cells from 20 to 120 min after irradiation either with photons at 2-10-20 Gy or with carbon ions at 2 Gy (at the National Centre for Oncological Hadrontherapy (CNAO), Pavia, Italy). We also evaluated the cell death and morphology changes induced by radiation treatment. Both FET and FCH are able to trace tumor behavior in terms of higher uptake for increased doses of radiation treatment, due to the upregulation of cells attempts to repair nonlethal damage. Our data suggest that both FCH and FET could be useful to analyze the metabolic pathways of glioblastoma cells before and after radiotherapy. Physicians will have to consider the different kinetics pathways of uptake concerning the two radiopharmaceuticals.